Теоретические аспекты и практические пути построения занятий по социально-бытовой ориентировке детей с интеллектуальной недостаточностью развития - Саруханян, К. А.; Яйлоян, А. В.
The main ways of creation of classes in a social-domest ic orintation of children with intellectual insuffi ciency of development are presented in article. Theoretical and practical aspects of the solution of this problem revealed.
Keywords: Личная гигиена